Replacement of dietary fish meal with Clostridium autoethanogenum meal on growth performance, intestinal amino acids transporters, protein metabolism and hepatic lipid metabolism of juvenile turbot (Scophthalmus maximus L.) - Zheng, Jichang; Zhang, Wencong; Dan, Zhijie; Zhuang, Yanwen; Liu, Yongtao; Mai, Kangsen; Ai, Qinghui (Frontiers in Physiology, 2022)
To evaluate the efficiency of Clostridium autoethanogenum meal (CAM) as an alternative for dietary fish meal, a 56-day growth experiment was performed on juvenile turbot (Scophthalmus maximus L.) with initial average weight of 9.13 ± 0.02 g. Six iso-nitrogenous and iso-lipidic diets were formulated with 0%, 15%, 30%, 45%, 60% and 80% dietary fish meal protein substituted by CAM protein, which were designated as CAM0 (the control group), CAM15, CAM30, CAM45, CAM60 and CAM80, respectively. No significant differences were observed in survival rate among dietary treatments (P > 0.05). The specific growth rate (SGR) was not significantly affected when replacement levels were less than 45% (P > 0.05). The feed intake (FI) was significantly linear reduced with increasing dietary CAM (P < 0.05), whereas no significant differences were observed in feed efficiency ratio (FER) among dietary treatments (P > 0.05). The apparent digestibility coefficient (ADC) of crude protein and most essential amino acids showed significantly linear increase with increasing dietary CAM (P < 0.05). Furthermore, with the increase of dietary CAM, the gene expression of intestinal peptide and amino acids transporters was first up-regulated and then down-regulated with significantly quadratic pattern (P < 0.05), which was similar to the expression of genes related protein degradation in muscle. For genes related to protein metabolism in liver and muscle, the expression of mammalian target of rapamycin (mtor) was not significantly affected by dietary CAM, while the general control nonderepressible 2 (gcn2) tended to be first up-regulated and then down-regulated with significantly quadratic pattern (P < 0.05). The lipid metabolism of turbot was also affected by high dietary CAM, evidenced by increased expression of hepatic genes related to lipogenesis as well as reduced expression of genes related to lipid oxidation and lipid transport. In conclusion, CAM can replace 45% fish meal protein in diet for juvenile turbot without adverse effects on growth performance. But excessive dietary CAM would result in significant growth reduction due to poor palatability as well as insufficient available small peptide and amino acids, and excessive lipid deposition would also occur in fish fed diets with high CAM.